Assessment of lubricating oil degradation in small motorcycle engine fueled with gasohol - Nakorn Tippayawong (2018)
Assessment of the degradation of lubricating oil was performed on the lubricants which had been used in a small motorcycle engine fueled with gasohol in comparison with the lubricants from gasoline-run engine. The lubricant properties examined in the assessment were lubricating capacity, viscosity and stability to oxidation. Lubricating capacity was evaluated by accelerated wear test on the Timken tester. Lubricating oils from gasohol-run engine appeared to produce about 10% greater wear than that made in oils from gasoline-run engine. There was no significant difference between the effect of gasohol and gasoline on the viscosity of the used lubricating oils. Moreover, no oxidation products in any used oil samples could be detected. © 2010.